Disturbance Process of Sandy Gravel Stratum Caused by Shield Tunneling and Ground Settlement Analysis - Nie Qingke (Frontiers Media S.A., 2021)
This paper analyzed the earth pressure, pore pressure, and surface settlement of the Luoyang urban rail transit tunnel in a sandy gravel stratum (Henan Province, China) under different burial depths by using field measurement methods. The results showed that the earth pressure as well as pore pressure of the soil layer above the working surface increased sharply and reached their maximum values when the cutter head of the shield gradually crossed the working surface. During the completion of synchronous grouting, the earth pressure and pore pressure increased slightly; when shield tunneling passed through the working surface, the earth pressure is smaller than the original earth pressure due to the unloading effect. The surface settlement curve above the tunnel took on a “V” shape after the completion of the left-side tunnel excavation, conforming to the normal distribution pattern. The surface settlement curve above the two tunnels took on a “W” shape after the completion of the right-side tunnel excavation, which is in good agreement with the proposed theoretical calculations. The findings of this study can help for better understanding the control of safety risk during shield construction.